THE MEDICINAL VALUE OF LEECHES - MEENAKSHI PRIYA (International Journal of Multidisciplinary Research and Studies, 2020)
In an era when many folk remedies are being rediscovered and the use of homeopathic and natural drugs is increasingly popular, it is not surprising to witness a revival of the use of leeches in medical practice. In the ancient world, leeches were used as one of several methods of bloodletting. The concept of removing vitiated blood in an attempt to restore health was a fundamental one, and instruments such as lancets, scarifiers and bleeding cups were in common use among apothecaries and surgeons. Tools for venesection were unearthed from archeological excavations of the Stone Age.’ Leeches were used for bloodletting and were applied to congested or inflamed parts of the body in conditions of engorged hemorrhoids, swollen testicles, laryngitis, prolapsed rectum and inflamed vulva. Compared to venesection, the use of leeches was considered a less painful procedure, in which a limited amount of blood could be removed.